2007
DOI: 10.1144/0016-76492007-017
|View full text |Cite
|
Sign up to set email alerts
|

The carbonate tectonic units of northern Calabria (Italy): a record of Apulian palaeomargin evolution and Miocene convergence, continental crust subduction, and exhumation of HP–LT rocks

Abstract: In northern Calabria (Italy), the metasedimentary succession of the Lungro–Verbicaro tectonic unit preserves mineral assemblages suggesting underthrusting to depths in excess of 40 km. Internal deformation of these rocks occurred continuously during the following decompression. Index mineral composition associated with progressively younger tectonic fabrics indicates that a substantial part of the structural evolution took place within the blueschist-facies P – T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 46 publications
6
75
0
Order By: Relevance
“…This is a nappe pile, which can be described as the superposition of three major structural elements that represent different paleogeographic domains: (i) The Apennine Units Complex made up of Mesozoic sedimentary and metasedimentary successions (Trias-Miocene) [47]; (ii) The structurally intermediate allochthonous Alpine Liguride nappe (Tithonian-Neocomian) made up of a series of Alpine metamorphic units including a Cretaceous-Paleogene metapelitic-ophiolitic-carbonate assemblage [41,46]; (iii) The Calabride Complex formed by Hercynian and pre-Hercynian gneiss, granite and metapelite. The Liguride nappe consists of HP-LT ophiolitic sequences, in which a metabasic and metaultramafic association constitutes the basis of a complex metasedimentary cover, ranging from pelagic to flyschoid types of sediments [41].…”
Section: Geological Settingmentioning
confidence: 99%
“…This is a nappe pile, which can be described as the superposition of three major structural elements that represent different paleogeographic domains: (i) The Apennine Units Complex made up of Mesozoic sedimentary and metasedimentary successions (Trias-Miocene) [47]; (ii) The structurally intermediate allochthonous Alpine Liguride nappe (Tithonian-Neocomian) made up of a series of Alpine metamorphic units including a Cretaceous-Paleogene metapelitic-ophiolitic-carbonate assemblage [41,46]; (iii) The Calabride Complex formed by Hercynian and pre-Hercynian gneiss, granite and metapelite. The Liguride nappe consists of HP-LT ophiolitic sequences, in which a metabasic and metaultramafic association constitutes the basis of a complex metasedimentary cover, ranging from pelagic to flyschoid types of sediments [41].…”
Section: Geological Settingmentioning
confidence: 99%
“…The tectonic sketch map reporting the main tectonic features is shown in the inset on the bottom left. The study area (Crati Basin) is indicated by the inset on the bottom centre (modified after Robustelli et al 2014 (Van Dijk et al 2000;Bonardi et al 2001;Butler et al 2004;Iannace et al 2007).…”
Section: Geological Settingmentioning
confidence: 99%
“…Tectonic units of the Chain Carbonate-Apennine Complex Prevalent Triassic dolostone and metalimestone (Monte Cocuzzo Unit), outcropping in 'tectonic windows' along the southern edge of the Coastal Chain horst, and Mesozoic to Langhian succession constituted by phyllites, metalimestone, dolostone and calcarenites and marls, with turbiditic strata (LungroVerbicaro Unit) (Iannace et al, 2007), outcropping in the north-western extremity of the study area.…”
Section: Lithostratigraphymentioning
confidence: 99%